Europe, India, and the limits of secularism - De Roover, Jakob (Religion and democracy reconceptualizing religion, culture, and politics in a global context, 2015)
Limits of liberal secularism -- Stories of liberal secularism -- The political theology of the two kingdoms -- Liberty, tyranny, and the divine order -- The enlightenment and the secular -- Religious toleration in British India -- Straitjackets of secularism